Clays and Clay Minerals, Vol. 58, No. 3, 327–339, 2010. - Guerra, Denis L.; Ferrreira, Josane N.; Pereira, Mario J.; Viana, Rubia R.; Airoldi, Claudio (The Clay Minerals Society, 2010)
The contamination of aquatic environments by toxic metals such as radionuclides is of great concern because of the tendency of those metals to accumulate in the vital organs of humans and animals, causing severe health problems. The objective of this study was to investigate the use of natural and modified magadiite clay as an adsorbent to remove Th(IV), U(VI), and Eu(III) from aqueous solutions. Magadiite from the Amazon region, Brazil, was modified chemically with 5-mercapto-1-methyltetrazole (MTTZ) using a multi-step or heterogeneous synthesis pathway. The natural and modified materials were characterized using 29Si and 13C nuclear magnetic resonance, scanning electron microscopy, nitrogen gas adsorption, and elemental analysis. The physical-chemical properties of the chemically modified magadiite sample were modified, e.g. the specific surface area changed from 35.0 to 678.9 m2 g-1. The ability of the magadiite to remove Th(IV), U(VI), and Eu(III) from aqueous solution was then tested by a series of adsorption isotherms adjusted to a Sips equation. The effects of properties such as pH, contact time, and metal concentration on the adsorption capacity were studied. The adsorption maxima were determined to be 7.5610-3, 9.8610-3, and 12.9610-3 mmol g-1 for Th(IV), U(VI), and Eu(III), respectively. From calorimetric determinations, the quantitative thermal effects for all these cations/basic center interactions gave exothermic enthalpy, negative Gibbs free energy, and positive entropy, confirming the energetically favorable conditions of such interactions at the solid/liquid interface for all systems.
Use Of Natural And Modified Magadiite As Adsorbents To Remove Th(iv), U(vi), And Eu(iii) From Aqueous Media - Thermodynamic And Equilibrium Study
gsccm58304-lim.pdf -- 580KB
Keywords: Periodicals; Geology; Calorimetry; Chemical Synthesis; Interfaces; Magadiite; Surface Properties; Thermodynamic Properties